Hypercolorimetric multispectral Imaging and Pulse Compression thermography as innovative combined techniques for painting investigation: the case of a detached wall painting by Pastura. Issue 1 (November 2020) - Agresti, G; Burrascano, P; Calabrò, G; Colantonio, C; Lanteri, L; Laureti, S; Melis, M; Pelosi, C; Ricci, M; Sfarra, S
Abstract: This contribution focuses the attention on an innovative approach in diagnostics of paintings, based on the combine use of two imaging techniques named Hypecolorimetric Multispectral Imaging (HMI) and Pulse Compression Thermography (PuCT) applied to a 15 th century wall painting, attributed to the Italian artist Antonio del Massaro, also known as Pastura. HMI technique is based on the simultaneous exploitation of the electromagnetic spectrum from the ultraviolet to the near infrared region. The acquisition, made under a standard metric, allows for characterizing the investigated surfaces in a more detailed way than the standard colorimetry. The system transforms any spectra in the range 300-1000nm into sevenfold hypecolorimetric coordinates. HMI guarantees very high radiometric (better than 95%) and colorimetric precision (better than ΔE = 2). PuCT is a thermography technique based on the use of coded modulated heating stimuli in combination with the pulse-compression technique. A PuCT scheme, based on coded LED excitation capable of optimizing the estimation of the impulse responses compared to the state-of-the-art PuCT literature has also been proposed. The combined use of HMI and PuCT recently revealed its potentiality in the investigation of important panel paintings by highlighting hidden details, mapping the conservation status, characterizing painting materials, etc. in a completely non-invasive way. Their combined capabilities are here tested on a wall painting representing the Madonna with the Child and the Saints Jerome and Francis, which was investigated during the restoration in the Laboratory in order to supply information about the materials and techniques.